Efficacy of oclacitinib (Apoquel®) compared with prednisolone for the control of pruritus and clinical signs associated with allergic dermatitis in client‐owned dogs in Australia. Issue 6 (11th August 2014) - Gadeyne, Caroline; Little, Peter; King, Vickie L.; Edwards, Nigel; Davis, Kylie; Stegemann, Michael R.
<x xml:space="preserve">Abstract</x> Background Oral glucocorticoids are widely used to reduce pruritus and dermatitis associated with allergic dermatitis. Data suggest that oclacitinib, a Janus kinase inhibitor, is a safe and effective alternative. Hypothesis/Objectives To evaluate the efficacy and safety of oclacitinib compared with prednisolone for the control of pruritus associated with allergic dermatitis in a single‐masked, controlled clinical trial with a randomized complete block design. Animals Client‐owned dogs (n = 123) with a presumptive diagnosis of allergic dermatitis and moderate to severe pruritus as assessed by the pet owner were enrolled. Methods Dogs were randomized to treatment with either oclacitinib (0.4–0.6 mg/kg orally twice daily for 14 days, then once daily) or prednisolone (0.5–1.0 mg/kg once daily for 6 days, then every other day) for 28 days. An enhanced visual analog scale (VAS) was used by owners to assess pruritus and by veterinarians to assess dermatitis, at all time points assessed. Results Both treatments produced a rapid onset of efficacy within 4 h. The mean reductions in pruritus and dermatitis scores were not significantly different between the treatments except on day 14, when reductions were more pronounced for oclacitinib than prednisolone (P = 0.0193 for owner pruritus scores; P = 0.0252 for veterinarian dermatitis scores). Adverse events were reported with similar frequency in both groups. Conclusion and clinical importance In this study, both oclacitinib and prednisolone provided rapid, effective and safe control of pruritus associated with allergic dermatitis, with substantial improvement in pruritus, reported by owners, and dermatitis, reported by veterinarians.